2021
DOI: 10.3390/jcm10153243
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Profiles and Cognitive Function from Adulthood to Old Age: Chasing a Golden Middle Way?

Abstract: With the demographic shift toward advanced ages, it is imperative to understand the biological mechanisms behind common, disabling age-related diseases such as cognitive impairment in its mild form to overt dementia. Hypertension, a major cardiovascular risk factor, is epidemiologically linked to vascular and Alzheimer-type dementia, with possible mechanisms being atherosclerotic macro- and microvascular damage leading to neuronal cell death, as well as proinflammatory events responsible for neurodegeneration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…In an Alzheimer's disease animal model, chronic brain stimulation enhances amyloid accumulation and induces epileptic activity [162]. It has been shown that raising the firing rate boosts Aβ production [163]. Tau protein may have a significantly bigger involvement in neuronal activity, and hence epileptiform activity, than previously anticipated.…”
Section: Epilepsymentioning
confidence: 98%
“…In an Alzheimer's disease animal model, chronic brain stimulation enhances amyloid accumulation and induces epileptic activity [162]. It has been shown that raising the firing rate boosts Aβ production [163]. Tau protein may have a significantly bigger involvement in neuronal activity, and hence epileptiform activity, than previously anticipated.…”
Section: Epilepsymentioning
confidence: 98%